WEB DESIGN AND WEB PROGRAMMING IN THE MODERN INTERNET WORLD - Fedorchuk, A.; Usata, O.; Nakonechna, O. (Municipal economy of cities. Series: «Economy science», 2023)
Modern web content development capabilities are undergoing characteristic changes due to the improvement of web technologies in programming. The origin of web technologies began in the early 80s of the last century when the Hypertext Transfer Protocol (HTTP) and the Hypertext Markup Language (HTML) made a significant contribution to the development of Internet capabilities. The web evolution, characterised by scientific and technological progress in information technology, has opened up new opportunities for the development of web programming, which has led to the emergence of programming languages, frameworks, cascading style sheets, and hypertext markup languages. This research aims to study and analyse the key aspects of web programming and web design with a combination of modern features of the Internet environment. To analyse web design, the article considers the possibilities of using the Bootstrap framework, which combines and contains the HTML5 hypertext markup language, CSS3 cascading style sheets, and the JavaScript programming language. Having analysed two web development technologies—front-end and back-end—we can conclude that the presentation level (front-end development) corresponds to the client side, with which the client can interact and where dynamic elements can be added to an HTML page using JavaScript with the visual definition of a web page using CSS. In the case of back-end development, the application layer corresponds to the server side, with which the client cannot interact, as the shell is hidden. Using the modern capabilities of the programming language, its code, and a set of auxiliary tools in website development, the paper presents a development algorithm where each stage contains separate processes and operations during website development, which makes it impossible for them to exist independently. Thus, tools for designing and laying out websites using modern technologies can greatly simplify the development process, which can create higher-quality web content.